2003
DOI: 10.1021/bm020135s
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Cellulose by Ceric(IV) Ion-Initiated Graft Copolymerization of N-Isopropylacrylamide

Abstract: Temperature-responsive cellulose has been obtained by graft copolymerization of N-isopropylacrylamide (NIPAAm) monomer using ceric ammonium nitrate (CAN) as initiator at 25.0 +/- 0.1 degrees C in acidic medium. Kinetic and grafting parameters were evaluated at different concentrations of NIPAAm ranging from 1.25 x 10(-3) to 12.5 x 10(-3) mol dm(-3) and varying concentrations of CAN from 1.5 x 10(-3) to 9.0 x 10(-3) mol dm(-3) at constant concentration of nitric acid (2.5 x 10(-2) mol dm(-3)). The graft copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 29 publications
4
109
0
Order By: Relevance
“…It should be noted that in the 2 nd series of experiments Soxhlet extraction was used to purify the gels despite the temperature of purification being higher than the phase transition temperature. Gupta et al [23] have also used Soxhlet extraction for removing ungrafted PNIPAAm homopolymer from grafted cellulose. It was expected that impurities become entrapped at higher cross-link ratio in the gel during Soxhlet purification, due to the high cross-link density, and collapsed structure of the gels during extraction.…”
Section: Results Of High-performance Liquid Chromatographymentioning
confidence: 99%
“…It should be noted that in the 2 nd series of experiments Soxhlet extraction was used to purify the gels despite the temperature of purification being higher than the phase transition temperature. Gupta et al [23] have also used Soxhlet extraction for removing ungrafted PNIPAAm homopolymer from grafted cellulose. It was expected that impurities become entrapped at higher cross-link ratio in the gel during Soxhlet purification, due to the high cross-link density, and collapsed structure of the gels during extraction.…”
Section: Results Of High-performance Liquid Chromatographymentioning
confidence: 99%
“…Following one of these two chemical pathways, polyesters such as polylactide or poly(e-caprolactone) have been grafted onto cellulose, [13] dextran, [14] alginate, [15] chitosan [16] and hyaluronan [17] resulting in amphiphilic copolymer structures. Vinyl monomers such as styrene, [18][19][20] methyl methacrylate, [21,22] vinyl acetate [23] and N-isopropylacrylamide [24] also have been polymerized along polysaccharide chains through conventional free radical methods [21,24] or more recently by living/controlled polymerization methods. [18][19][20]22,23] The reverse approach, namely the grafting of polysaccharide chains onto synthetic polymer backbone has been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al studied the activation energy for graft copolymerization of NIPAAm onto cellulose by using CAN. [58] They found that the grafting was increased below LCST of PNIPAAm, and obtained a low energy of activation (18.0 kJ Á mol À1 ) within the temperature range of 10-35 8C. The NIPAAm-g-cellulose has shown significant improvement in its properties such as thermal stability, water absorbency, and degree of swelling.…”
Section: Hydrogels Prepared Using Initiatorsmentioning
confidence: 99%